Total Endoprosthesis Versus Lundborg´s Resection Arthroplasty for the Treatment of Trapeziometacarpal Joint Osteoarthritis. Issue 4 (April 2018) - Erne, Holger; Scheiber, Claudia; Schmauss, Daniel; Loew, Steffen; Cerny, Michael; Ehrl, Denis; Schmauss, Verena; Machens, Hans-Guenter; Muhl, Philipp
Abstract : Background: There exist various operative approaches for the treatment of trapeziometacarpal joint osteoarthritis. The aim of this study was to compare the results of Lundsborg's resection arthroplasty (RA) with implantation of a total endoprosthesis. Patients and Methods: In this 2-center study, we retrospectively analyzed 71 patients with symptomatic osteoarthritis of the carpometacarpal I joint stage III according to the Eaton-Littler classification. Thirty-two patients underwent a Lundsborg's RA group, and 39 patients received a total endoprosthesis of the carpometacarpal I joint (TEP group). We evaluated operative time, DASH score, postoperative time until resolution of symptoms, pain level, pinch force, and satisfaction with the treatment. Results: Both groups had a similar mean length of follow-up of 42 months (TEP group) and 36 months (RA group). The final DASH score was significantly better in the TEP-group (10.1 versus 21.5 in the RA group; P ⩽ 0.05). Also, the time interval from surgery till absence of any pain (1.5 versus 5.9 months) and the time of inability to work (6 versus 21 weeks) were significantly shorter for the TEP group compared with the RA group ( P ⩽ 0.05). The pinch force, pain intensity, and the satisfaction with the treatment were comparable ( P > 0.05). The duration of the operation was significantly shorter in the RA group (31 min versus 65 min in the TEP group; P ⩽ 0.05). Conclusion: Both techniques resulted in improved function of the operated hand and a clear reduction of symptoms. However, the implantation of a total endoprosthesis seems to have advantages, given a significantly better DASH score and a significantly shorter time until resolution of symptoms.